Stickleback (Gasterosteus aculeatus) marine heatwave experiment: F0 adult size and fecundity traits, F1 offspring growth, behavior and survival, and F2 offspring egg size, clutch size, and hatchling length - Helen Spence-Jones; Lisa N S Shama (PANGAEA, 2025)
The data contains information about marine stickleback (Gasterosteus aculeatus) used in a multi-generation laboratory breeding experiment investigating the effects of heatwaves on marine species. Adult stickleback were caught by trawling in the Sylt-Romo Bight (Lat: 55.0252; Long: 8.436) between 3 Feb and 10 March 2022. Fish were brought to the laboratory at the AWI Wadden Sea Station Sylt and used as breeding adults for a multi-generation laboratory experiment investigating the effects of marine heatwaves on stickleback fitness-related traits. These F0 generation wild-caught adults (males and females) were acclimated to three heatwave scenarios (no heatwave control, single heatwave or double heatwave) for three months before breeding (starting 12 June 2022) via artificial fertilization. We measured several fecundity traits for each clutch of fertilized eggs including clutch size (total number of eggs), average egg size (diameter (mm)), fertilization success and hatching success. The diameter (mm) of all eggs in a clutch was measured to estimate average egg size. Each clutch of fertilized eggs was then split among the same three heatwave scenarios, and growth of the F1 offspring in the 9 heatwave treatment combinations was assessed at hatching, 30 days, 60 days and 90 days post-hatch. F1 offspring were also used to estimate two behavior traits (activity rate and exploration), and both short-term (up to 90 days post-hatch) and long-term (until F1 adult breeding) survival. When F1 offspring were ca. two years old, they were used as breeding adults (between 19 April- 28 May 2024) for the F2 generation, and the same fecundity traits as in the F0 were measured (clutch size, average egg size, fertilization success, hatching success), as well as F2 hatchling size.